Extending the bargaining power model: Explaining bargaining outcomes among nations, MNEs, and NGOs - Nebus, James; Rufin, Carlos (Journal of International Business Studies, 2010)
Participants in international bargaining include different types (nation states, MNEs, NGOs, and multilateral organizations) and different numbers of these actors. Our theoretical contribution is to extend the bargaining power paradigm with a framework that models bargaining in this complex environment as a network. The configuration of supports and constraints among all participating actors in the bargaining environment is captured in the structure of the network. Antecedents of an actor's bargaining influence in the network include the actor's basis of power, network position, bargaining outcome preferences, and motivation to influence bargaining. The network bargaining power (NBP) model uses network theory to build upon and integrate insights from previous literature in a way that allows us to simultaneously apply these different insights to explain bargaining outcomes. These insights include effects of coalitions, strategies of less powerful actors leveraging more powerful allies, integration of international and domestic politics, and applicability to MNE-related issues beyond FDI. Finally, we illustrate NBP in a scenario of privatized utilities in the Dominican Republic, in which the bargaining power outcome predicted by NBP differs from that of the canonical bargaining power perspective.